Association of Peripheral Interleukin-6 with Global Cognitive Decline in Non-demented Adults: A Meta-Analysis of Prospective Studies - Bradburn, Steven; Sarginson, Jane; Murgatroyd, Christopher A. (Frontiers in Aging Neuroscience, 2018)
Background: Elevated biomarkers of systemic inflammation have been reported in individuals with cognitive decline, however, most of the literature concerns cross-sectional analyses that have produced mixed results. This study investigates the aetiology of this association by performing meta-analyses on prospective studies investigating the relationship between baseline interleukin-6 (IL-6), an established marker of peripheral inflammation, with cognitive decline risk in non-demented adults at follow-up. Methods: We reviewed studies reporting peripheral IL-6 with future cognitive decline, up to February 2017 by searching the PubMed, Science Direct, Scopus and Google Scholar databases. Studies which contained odds ratios (ORs) for the association between circulating baseline IL-6 and longitudinal cognitive performance in non-demented community dwelling older adults were pooled in random-effects models. Results: The literature search retrieved 5,642 potential articles, of which 7 articles containing 8 independent ageing cohorts were eligible for review. Collectively, these studies included 15,828 participants at baseline. Those with high circulating IL-6 were 1.42 times more likely to experience global cognitive decline at follow-up, over a 2 – 7-year period, compared to those with low IL-6 (OR 1.42, 95% CI 1.18 – 1.70; p < 0.001). Subgroup and sensitivity analyses suggests that this association is independent of the study sample size, duration of follow-up and cognitive assessments used. Conclusions: These results add further evidence for the association between high peripheral inflammation, as measured by blood IL-6, and global cognitive decline. Measuring circulating IL-6 may be a useful indication for future cognitive health.